(untitled) (Journal of Naval Architecture and Marine Engineering, 2013)
Due to the increase of maritime transportation volume day by day it is necessary to design a ship hull having large carrying capacity with low resistance. In case of slow moving ships, usually wave breaking occurs in front of bow. A considerable portion of resistance occurs due to the energy dissipation of such wave breaking in case of Ultra Large Block coefficient Ship (ULBS) suggested by the authors. The key objective of this research work is to investigate the relationship between bow wave breaking and free surface disturbance function that may be used as a parameter for numerical prediction of bow wave breaking. In this regard, the experiments and numerical calculations have been carried out for six models of ULBS. From the results, it can be concluded that the wave breaking area in front of bow increases with the increase of surface integral of the square of free surface disturbance function, Froude number and block coefficient. DOI: http://dx.doi.org/10.3329/jname.v10i2.16104